Prof. Erino Angelo Rendina: keep passionate and dream big - Yuan, Amber (Journal of Thoracic Disease, 2018)
The AATS Focus on Thoracic Surgery: Lung and Esophageal Cancer was successfully held in Guangzhou, China, from 3rd to 4th of November in 2018. It was a fantastic academic journey, gathering many renowned surgeons and scholars from all around world to exchange new ideas and experiences.